Geomorphometric environmental fragility of a watershed: a multicriteria spatial approach - Amorim, Amanda Trindade [UNESP]; do Nascimento Lopes, Elfany Reis; de Sousa, Jocy Ana Paixão [UNESP]; de Cassia Ferreira da Silva, Rita [UNESP]; de Souza, José Carlos; Lourenço, Roberto Wagner [UNESP] (Springer Nature, 2021)
Knowledge and understanding of the functioning of watersheds is essential for constructing future scenarios that aim to minimize instability. However, new approaches including variables, methods, and techniques into traditional methodologies contribute to environmental planning and management of such territorial units. This study aims to propose a model based on a multicriterion spatial approach for the analysis of the geomorphometric environmental fragility of watersheds. This study was conducted in the Murundú-Paiol watershed, located in the state of São Paulo, Brazil. Morphometric, geological, pedological, hypsometric, slope, land use, and land cover data were evaluated and integrated using geotechnologies for processing and analytical hierarchy process (AHP) considering a weighted linear combination for an integrated spatial analysis of the watershed. The study area shows a greater predisposition to fragility in areas of flat and smooth reliefs, especially around the main river, where there is a greater presence of anthropic areas. The methodology proposed here, which uses a multicriterion spatial approach and AHP, combined with technical and scientific data, allows replicating the model to another watersheds. Modeling was validated in a cooperative way using an in-field, traditional method. The watershed evaluated showed that 49.13% and 26.83% of lands have medium and low fragility, respectively, while about 17% of lands have a high fragility and their management should be a priority. Modeling correlates strongly and positively with fragility class detailing, and field areas corroborate the model proposed here. This evidenced a robust analysis of factors that affect the geomorphometric environmental fragility of watersheds. The method is efficient in contributing to environmental planning and management of this territorial unit.
Keywords: Environmental degradation; Geomorphometric fragility; Geotechnologies; Integrated analysis; Water resource